Media Literacy, active citizenship and sustainable democracy: a case study of Slovenia - Uršič Erika Džajić; Jurak Alenka Pandiloska (Politics in Central Europe, 2023)
This article shares research findings to support the case for media literacy education to facilitate robust media engagement by Slovenian citizens. It shares the outcomes of a project MELIA Observatory funded by the Interreg Danube, which brought together researchers, practitioners, professionals, civil society, and key stakeholders, including journalists, teachers, students, librarians and information professionals. The article aims to evaluate state-of-the-art of media literacy and engaged social responsibility within sustainable democracy in Slovenia. We first present public institutions involved in Slovenian where we include media regulation with a focus on media literacy and its implications for active citizenship and sustainable democracy. Secondly, laws governing all aspects of media are presented, again emphasizing the connection between media literacy and active citizenship which is most evident here. From the findings, media education requires a “reboot” to promote critical resilience through a sophisticated academic deconstructionism of media mixed with theorised production of the same media before it can be successful. Slovenia as a representative partner of the MELIA Observatory is a new democracy, and its democratic consolidation processes have been problematic, as seen by issues of political aspects, hate speech, discrimination, misinformation, and weak media freedom regimes.